A process-oriented model of pelagic biogeochemistry for marine systems. Part II: application to a mesotidal estuary - Mateus, M. (2019)
The main goal of this study is to use an integrated ecosystem model to study the role of physical, chemical and environmental parameters on the biogeochemistry of the Tagus estuary, the main estuarine system in Portugal. This work was developed as part of EU-funded INSEA project and tried to accomplish two major aims: (1) the development and implementation of a coupled modeling system capable of reproducing all the major characteristics both in physical and biological environments, and (2) to create a coastal management system based on the efficient integration of observations and biophysical models. Our results suggest that both aims were met. In this study we have used a 2D hydrodynamic application coupled to a complex ecological model presented in a companion paper which captures the state of the art of marine ecological models, and also developed during the project. Special emphasis is given to the processes governing temporal and spatial patterns of both phytoplankton and bulk properties, and the physical–biological interactions shaping their variability. The results shown in this paper are indicative of a reasonable performance of the model. It captures the complexity of the Tagus estuary and provides reasonable estimates of the biomass trends of a highly dynamic and interactive community.